Synthesis of Biogasoline from Used Palm Cooking Oil Through Catalytic Hydrocracking by Using Cr-Activated Natural Zeolite as Catalyst - Jujarama; Wijaya, Karna; Shidiq, Mohammad; Fahrurrozi, Mohammad; Suheryanto (Asian Journal of Chemistry, 2014)
This study was concerning on production of biogasoline from used palm cooking oil through Cr-activated natural zeolite catalyzed hydrocracking. Natural zeolite was activated using 6M hydrochloric acid. The precursor Cr(NO3)3·9H2O was impregnated on activated natural zeolite. Catalysts characterization including catalysts crystallinity using X-ray diffraction and catalysts porosity using the BET method. The used palm cooking oil was vaporized at 350 °C and then flowed into the batch reactor which temperature was set at 400, 450 and 500 °C. Hydrogen was feed into the batch reactor at a constant rate of 40 mL/min. The variation of reactor conditions was with no catalysts, with zeolite catalysts and with catalyst Cr-activated natural zeolite. The product was then condensed in a water cooled condensor. The condensed products was analyzed using GC, GC-MS, ASTM D 1298, ASTM D 130, ASTM D 323 and ASTM D 86/99a to determine the formed fraction. The results show that the acid activation and impregnation reaction at zeolite samples can improve it crystallinity, surface area and pore radius. Active natural zeolite sample has a specific surface area of 43.815 m2/g while Cr-activated natural zeolite has a specific surface area of 89.514 m2/g. The highest conversion was gained by using Cr-activated natural zeolite catalysts at 500 °C reactor temperature which produced 76.44 % liquid product and 23.25 % yield.